Effects of Du Meridian Moxibustion Combined with Mild Moxibustion on Female Pelvic Floor Myofascial Pain Syndrome: A Retrospective Cohort Study. (15th November 2022) - Wei, Yehong; Chen, Xufeng; Wang, Tianyu; Dong, Xianna; Zhu, Zheng
Abstract : Objective . This study aimed to investigate the efficacy and safety of moxibustion in the treatment of pelvic floor myofascial pain syndrome. Methods . A total of 80 women with pelvic floor myofascial pain syndrome (cold coagulation and blood stasis type) were included in this retrospective study and divided into a moxibustion group and a drug treatment group. Patients who received Celebrex oral analgesia, health education, and lifestyle improvement were included in the drug treatment group. The patients that received Du meridian moxibustion combined with mild moxibustion, health education, and lifestyle improvement were included in the moxibustion group. The comparison of pelvic pain, the TCM clinical symptom score, and the curative effect was made between the two groups before treatment and after 1–3 weeks of treatment, respectively. Results . An intragroup comparison showed a stepwise decrease in the VAS score and the TCM clinical symptom score of the two groups during the treatment. An intergroup comparison revealed that the VAS score of the moxibustion group was lower than that of the drug treatment group, while TCM clinical symptoms and clinical efficacy significantly improved in the moxibustion group compared to those in the drug treatment group (P < 0.05 ). Conclusion . Du meridian moxibustion combined with mild moxibustion alleviates pelvic floor myofascial pain syndrome, thus helping improve women's quality of life and providing patients with a more effective and safer treatment plan.